Literary forms of trauma. Horror stories, fantasy stories and State terrorism. Reflections on 77, by Guillermo Saccomanno (Anclajes, 2025)
There are several links between terror genre and fantasy stories about State terrorism during the latest Argentinean dictatorship. The main objective of this paper is to explore these links throw the construction of a theoretical framework, writers statements in public interviews and the literary text 77 (2008) by Guillermo Saccomanno. The concepts of extreme situations and feeling structures allow us to structure the hypothesis. The link that unites these concepts and the generic is the traumatic nature of the events: in the face of a certain void of language and symbolization generated by the experience of extreme situations, the cracks inherent to terror and the fantastic are conducive to reading, in key literary and from the structures of feeling, of reality.
Keywords: Guillermo Saccomanno; Literary Criticism; Pos-dictatorship; Argentina; 21st century